A Study of Cultural Interaction and Linguistic Contact Approaching Chinese Linguistics from the Periphery - Uchida, Keiichi (2017)
This study is an attempt to reorient the field of Chinese linguistics from the perspective of the new field of cultural interaction studies. The author, approaching Chinese linguistics from the periphery, examines such topics as the spread of Western learning and linguistic contact and Westerners' study of Chinese: He studies materials produced by Western missionaries and Ryukyuan materials to show the validity and usefulness of Chinese linguistics in the field of cultural interaction studies. In addition, he looks at cultural interaction through illustrations.